(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This study aims at investigating the effect of using guided discovery with instructional aids on developing writing skill for intermediate schools.To achieve the aim of the present study, the following hypothesis has been used: There are no statistically significant differences at ( < 0.05) between the mean scores of the experimental group who is taught writing skill according to guided discovery with instructional aids and the control group who is taught according to the traditional way in the post test. The present study is limited to the second intermediate female students in Al- Amal secondary school for girls in Baqubah city for the academic year 2018/2019. The sample of this study consists of 40 students as the experimental group and 38 as the control group. Then, it is insured that the two groups are equal through a statistical manipulation of a number of variables such as age, writing skill in the previous year, and writing skill (spelling and punctuation) on the pretest. Pre and post-tests are designed, and the validity of the tests and the lesson plans has been achieved by exposing them to jury members. The reliability of the test have been achieved by using Kuder Richardson-20 formula (0.83). Statistical analysis of data achieved through the test which standard deviation indicates that there are statistically significant differences between the mean scores of the two groups in favour of the experimental group in the post test. The researcher concludes that using guided discovery approach with instructional aids is proven to be more fruitful and effective in promoting the students’ able and attention to writing easily and to give the students more opportunities than those in the textbook.